2019
DOI: 10.14414/jebav.v22i1.1400
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee characteristics and earnings management practices

Abstract: This study revisits the effectiveness of the audit committee independence and expertise in preventing earnings management practices.  Studies in other countries that have relatively stricter regulations showed the audit committee independence was effective to prevent earnings management.  Arguably, the practice may be different in Indonesia whose regulation is considerably more lenient.  On the other hand, studies related to audit committee expertise is rarely done in Indonesia.  This study utilized two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…A. Setiawan et al, 2020;Siagian and Siregar, 2018). However, these results are not in line with other studies that did not find the effect of the audit committee on earnings quality; this result is generally thought to be due to the lack of audit committee supervision as well as the lack of power the audit committee has in overseeing management so that it cannot carry out its functions optimally (Dewi and Mita, 2019;Halim, 2022;Kawedar et al, 2021;Nelwan and Tansuria, 2019;Savka, 2019).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A. Setiawan et al, 2020;Siagian and Siregar, 2018). However, these results are not in line with other studies that did not find the effect of the audit committee on earnings quality; this result is generally thought to be due to the lack of audit committee supervision as well as the lack of power the audit committee has in overseeing management so that it cannot carry out its functions optimally (Dewi and Mita, 2019;Halim, 2022;Kawedar et al, 2021;Nelwan and Tansuria, 2019;Savka, 2019).…”
Section: Introductionmentioning
confidence: 82%
“…The absence of a significant effect of the audit committee on earnings quality is thought to be due to not only the lack of supervisory function carried out by the audit committee but also the lack of power possessed by the audit committee in supervising management so that its function does not run well (Dewi & Mita, 2019;Halim, 2022;Kawedar et al, 2021;Nelwan & Tansuria, 2019;Savka, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Oradi and Izadi (2020) found that audit committee independence minimises the firm's ability to restate financial statement. Furthermore, Nelwan and Tansuria (2019) argued that an independent audit committee is an effective tool to constrain managers' misbehaviour. As mentioned earlier, the Code of Corporate Governance in UAE stipulates that the audit committee shall consist of at least three members, and at least two of them should be independent members.…”
Section: Audit Committee Sizementioning
confidence: 99%
“…In this model, a number of control variables are included because most prior literature finds these variables have an effect on earnings management (Nelwan & Tansuria, 2019;Alhadab et al, 2020;Mnif & Cherif, 2020). These control variables include firm size, firm profitability and firm leverage.…”
Section: Firm Leverage Levementioning
confidence: 99%
See 1 more Smart Citation